Peptide-MHC-Based Nanomedicines for the Treatment of Autoimmunity: Engineering, Mechanisms, and Diseases - Serra, Pau; Santamaria, Pere (Frontiers in Immunology, 2021)
Development of autoimmunity results from a breakdown of immunoregulation and involves cellularly complex immune responses against broad repertoires of epitope specificities. As a result, selective targeting of specific effector autoreactive T- or B-cells is not a realistic therapeutic option for most autoimmune diseases. Induction of autoantigen-specific regulatory T-cells capable of effecting bystander (dominant), yet tissue-specific, immunoregulation has thus emerged as a preferred therapeutic alternative. We have shown that peptide-major histocompatibility complex (pMHC)-based nanomedicines can re-program cognate autoantigen-experienced T-cells into disease-suppressing regulatory T-cells, which in turn elicit the formation of complex regulatory cell networks capable of comprehensively suppressing organ-specific autoimmunity without impairing normal immunity. Here, we summarize the various pMHC-based nanomedicines and disease models tested to date, the engineering principles underpinning the pharmacodynamic and therapeutic potency of these compounds, and the underlying mechanisms of action.